2003
DOI: 10.1128/jvi.77.4.2452-2458.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Human Herpesvirus 6 U100 Gene Product Is the Third Component of the gH-gL Glycoprotein Complex on the Viral Envelope

Abstract: The human herpesvirus 6 (HHV-6) variant A U100 gene encodes the third component of the glycoprotein H (gH)-glycoprotein L (gL)-containing complex. Glycosidase digestion analysis showed that the U100 gene products are glycoproteins consisting of an 80-kDa protein with complex N-linked oligosaccharides and a 74-kDa protein with immature, high-mannose N-linked oligosaccharides. Based on these characteristics, we designated the U100 gene products glycoprotein Q (gQ). Only the 80-kDa form of gQ was coimmunoprecipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 46 publications
(41 reference statements)
2
43
0
Order By: Relevance
“…However, our findings must be considered in terms of the well known association of HHV-6 gH with gL (9, 12-16) and the recent demonstration that these glycoproteins form a trimolecular complex with gp82-gp105, in particular with a minor 80-kDa species representing the mature form with complex N-linked oligosaccharides (20). Moreover, subsequent binding studies with a soluble CD46 construct suggested that the receptor associates with the gH/gL/gp82-gp105 trimolecular complex (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our findings must be considered in terms of the well known association of HHV-6 gH with gL (9, 12-16) and the recent demonstration that these glycoproteins form a trimolecular complex with gp82-gp105, in particular with a minor 80-kDa species representing the mature form with complex N-linked oligosaccharides (20). Moreover, subsequent binding studies with a soluble CD46 construct suggested that the receptor associates with the gH/gL/gp82-gp105 trimolecular complex (43).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gB (the most highly conserved glycoprotein among herpesviruses) and another glycoprotein, gp82-gp105, (thus far found only in HHV-6 and the related ␤-herpesvirus, HHV-7) appear to be critical for the fusion/entry process, as specific antibodies against these proteins block both virus infectivity and syncytia formation (17)(18)(19). Recently the gp82-gp105 glycoprotein has been shown to be associated with gH-gL complexes in infected cells and virions, and the designation gQ was proposed (20). At present, the precise roles of individual HHV-6 glycoproteins and their possible interplay in the infection process remain poorly understood.…”
Section: Human Herpesvirus 6 (Hhv-6)mentioning
confidence: 99%
“…Recently, gH-gL complexes of two betaherpesviruses, HCMV and human herpesvirus 6 (HHV-6), were found to also associate with a third viral glycoprotein, gO or gQ, respectively (7,19); these arrangements mirror the EBV gH-gL-gp42 interactions. Comparison of the sequences for EBV gp42 with those for gO and gQ does not reveal any obvious similarities.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridoma clones producing MAbs were established from the splenocytes of mice immunized with a purified recombinant protein or UVinactivated HHV-6 virions as described previously (11). MAbs recognizing gQ1 were established as described previously (3,25). The MAb designated BgQ1-202 was raised against recombinant protein BgQ1-N. BgQ1-N was created by the following procedure.…”
Section: Methodsmentioning
confidence: 99%